Maizura Ciwawa Boutique’s Sale and Stock Management System - Md Fadzli, Nur Amira Najiha; Ab. Aziz, Ruhaya (Applied Information Technology And Computer Science, 2024)
Maizura Ciwawa Boutique is a clothes and cosmetic boutique since 23 March 2015 which only located at Taman Sri Pulai Perdana, Johor. Maizura Ciwawa Boutique’s Sale and Stock Management System is a web-based system developed to facilitate the buying process for the customers and help the administrator to organize data of the boutique. The boutique also wishes to expand the business through the Internet. A manual system was used where it arises many problems such as manually updating data which is time consuming and need to physically come to the boutique which cost a lot. The waterfall model is used in this project where it involved requirement analysis, design, development, testing and maintenance. Every phase is important as it helps in developing the system properly and efficiently. This system consists of several modules which are login, profile, manage item, order, payment, manage sale, tracking item, live chat, and report module. Hopefully in the end, this system may help in increasing boutique sales.